Meditation as an Adjunct to the Management of Multiple Sclerosis. (1st July 2014) - Levin, Adam B.; Hadgkiss, Emily J.; Weiland, Tracey J.; Jelinek, George A.
Abstract : Background . Multiple sclerosis (MS) disease course is known to be adversely affected by several factors including stress. A proposed mechanism for decreasing stress and therefore decreasing MS morbidity and improving quality of life is meditation. This review aims to critically analyse the current literature regarding meditation and MS. Methods . Four major databases were used to search for English language papers published before March 2014 with the terms MS, multiple sclerosis, meditation, and mindfulness. Results . 12 pieces of primary literature fitting the selection criteria were selected: two were randomised controlled studies, four were cohort studies, and six were surveys. The current literature varies in quality; however common positive effects of meditation include improved quality of life (QOL) and improved coping skills. Conclusion . All studies suggest possible benefit to the use of meditation as an adjunct to the management of multiple sclerosis. Additional rigorous clinical trials are required to validate the existing findings and determine if meditation has an impact on disease course over time.